Talbot photolithography optimization with engineered hybrid metal-dielectric mask: High-contrast and highly-uniform Talbot stripes; Optics and Laser Technology; Vol. 148 - Geynts Yu. E. Yury Elmarovich (2022, 2022)
Title screen